PHYSICAL ACTIVITY AND EXERCISE AS A BASIC PREVENTIVE MEASURES FOR CURRENT RISK FACTORS - Kumar, Dr. Jatinder; Bhardwaj, Dr. Rajesh Kumar (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
Physical education is a special method to reduce the risk of developing diabetes, high blood pressure, heart disease and cancer. For children and young people being active helps reduce the risk of developing these diseases in later life too. In today’s trend of speedy life people have chosen a sedentary life style which is totally against health and may affect it very badly. In this context, the best treatment and remedy for this sedentary life style is nothing but physical exercise itself. It is the only source that requires the number of means and methods to involve people in active movement process to access their health through sports or yoga. It is used as a supplement to remain fit and flexible. The relation between physical education and health science is based on the physical activity and exercise. In fact, it provides the number of ways to change the status of health in our nation towards betterment that facilitates the protection and prevention for the health of whole population. It is being said that prevention is better than cure and physical education acts as the same. In another sense, health becomes the crucial issue for present time because people are often seen obese, having high cholesterol level, diabetes, heart disease and high blood pressure is common. By this regard, researchers find the solution for this big cause and reach at the point that physical education is the only medium to prevent these causes of diseases. This makes it clear that sportsperson and athletes have very less chance of common diseases that is because they are active in their movements and exercise.